Sistem Layanan Pemesanan Kalibrasi Berbasis Web: Studi Kasus PT. Global Quality Indonesia - Catur Muhammad Nugroho; Kartini (Prosiding SISFOTEK, 2024)
Information technology has become an integral part of various aspects of life, including the industrial world. PT. Global Quality Indonesia, a company engaged in calibration services for measuring instruments, is also benefiting from the positive impact of information technology development. PT. GQI has hundreds of customers spread across Indonesia. According to information gathered in 2023, PT. Global Quality Indonesia has provided calibration services for 3,251 orders, calibrating a total of 22,341 instruments. The main challenge faced is the service system which still relies on email for communication and orders. The use of email often results in a backlog of messages that are difficult to respond to promptly, thereby hindering the service process. Additionally, the company's website is not yet optimized to provide information and facilitate orders, limiting customer access to online calibration service bookings. The proposed solution is the development of a web-based ordering system. This will make it easier for customers to place orders and record order data on the website, and for the admin to manage data more efficiently, handling calibration requests, invoices, progress updates, and certificate issuance. This research uses the fishbone method for problem analysis and data collection, followed by system development using the SDLC Waterfall method. Based on the research and implementation, the resulting system can enhance the calibration services at PT. Global Quality Indonesia.